Silicon-carbon material and preparation method thereof, porous carbon substrate, negative electrode material and battery

By homogeneously doping phenolic resin and pre-carbonized biomass carbon precursor in the porous carbon substrate, carbon-based particles with complementary structures are formed, and the expansion problem of silicon carbon anode material during circulation and the problem of insufficient contact between conductive agents is solved, thereby achieving efficient battery performance and reducing production costs.

CN119812286AActive Publication Date: 2025-04-11WANXIANG 123 CO LTD

Patent Information

Application Number
CN202510230976.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-04-11
Estimated Expiration
2045-02-28

AI Technical Summary

Technical Problem

The existing silicon carbon negative electrode materials have expansion problems during circulation, resulting in a decline in battery performance, and the conductive agent and binder are not in close contact with the particles, which affects the long-cycle performance of the material.

Method used

By homogeneously doping phenolic resin and pre-carbonized biomass carbon precursors in the porous carbon substrate, carbon-based particles with spherical and block-like structures are formed, combined to increase the fill density and structural strength of the material, and enhance the binding force with the conductive agent and the binder.

Benefits of technology

The excellent cycle performance and conductivity of silicon-carbon materials are achieved, which reduces production costs and improves resource utilization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812286A_ABST
    Figure CN119812286A_ABST
Patent Text Reader

Abstract

The invention provides a silicon-carbon material and a preparation method thereof, a porous carbon substrate, a negative electrode material and a battery, and relates to the technical field of battery materials. The core point provided by the invention is controllable synthesis of the porous carbon substrate in the silicon-carbon material, a phenolic monomer and an aldehyde monomer are polymerized in the presence of a catalyst and a dispersing agent, meanwhile, a doping agent and a pre-carbonized biomass carbon precursor are added into a solution, the phenolic resin formed by polymerization is of a spherical structure, and the silicon-carbon composite material is obtained. Homogeneous doping of elements is completed in the synthesis process, the added biomass carbon precursor is of a blocky structure, matching of carbon-based particles of different structures can better exert respective beneficial effects and complement each other, the battery performance is comprehensively improved, and the battery has excellent cycle performance and conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to silicon-carbon materials and preparation methods thereof, porous carbon substrates, negative electrode materials and batteries. Background Art

[0002] Silicon-based anodes have become the most promising next-generation anode materials to replace graphite due to their high theoretical capacity, low lithium insertion potential, and abundant resources. With the vigorous development of semi-solid batteries and low-altitude economy, silicon-based anodes will usher in more opportunities. From the development history of silicon anodes, it has generally gone through several stages from traditional sand-milling silicon-carbon anodes, silicon-oxygen anodes to new deposition silicon-carbon anodes. Among them, the new deposition silicon-carbon, due to its unique structure and technology, has alleviated the expansion problem of silicon-based anodes to the greatest extent, becoming the mainstream development direction and widely recognized by academia and industry.

[0003] The design idea of ​​the new silicon-carbon negative electrode is to first prepare a porous carbon substrate, and then decompose the silicon source inside the pores of the porous carbon to form nano-silicon particles. By controlling the size of the silicon particles and making them amorphous, and reserving a certain amount of expansion space on the porous carbon substrate, the volume effect of the silicon-carbon material is effectively alleviated, which greatly improves the material's cycle performance. The selection of raw materials for the carbon substrate and the control of the activated pore structure are crucial, which determine the overall performance of the new silicon-carbon material. The resin-based carbon substrate has become a research hotspot due to its advantages such as few impurities and high compaction density. Researchers tend to synthesize spherical porous carbon substrates because they have high filling density, good fluidity, and uniform force for lithium insertion expansion. However, perfect spherical particles may not be in close contact with conductive agents and binders due to their smooth surface.

[0004] Patent CN 118908209A uses phenol source, dispersant, formaldehyde, stabilizer, activator and catalyst as main raw materials to synthesize phenolic resin-based microspheres at room temperature, and then obtains phenolic resin-based porous carbon spheres through carbonization and activation. The product has the characteristics of high monodispersity, no adhesion, high specific surface area, etc., but there may also be risks due to smooth particle surface and insufficient contact between the conductive agent and the binder.

[0005] Patent CN 118754119B discloses a method for preparing heterogeneous element-doped carbon materials. By doping with non-metallic and metallic heterogeneous elements in a specific order, the dynamic mechanical properties of lithium ions and electrons are improved, while the breakage of composite material particles during charging and discharging is suppressed and the interface stability is improved. However, there is also the problem of poor doping uniformity, and the improvement of dynamic performance is limited. At the same time, there are also problems such as many added ingredients, difficulty in synthesis, and difficulty in large-scale production. Summary of the invention

[0006] The present invention aims at the deficiencies of the prior art and provides a silicon-carbon material and a preparation method thereof, a porous carbon substrate, a negative electrode material and a battery. The core point lies in the controllable synthesis of the porous carbon substrate. Phenolic monomers and aldehyde monomers are polymerized in the presence of a catalyst and a dispersant. At the same time, a dopant and a pre-carbonized biomass carbon precursor are added to the solution. The phenolic resin formed by the polymerization is a spherical structure, and the homogeneous doping of elements is completed during the synthesis process. The added biomass carbon precursor is a block structure. The combination of carbon-based particles of different structures can better exert their respective beneficial effects, complement each other's strengths and weaknesses, and comprehensively improve performance. In addition, the biomass carbon precursor can also provide reactive groups to partially replace the amount of phenolic and aldehyde monomers, thereby greatly reducing production costs while improving resource utilization.

[0007] In a first aspect, the present application provides a porous carbon substrate:

[0008] A porous carbon substrate comprises a phenolic resin, a biomass carbon precursor obtained by pre-carbonizing a biomass carbon material, and a dopant dispersed in the porous carbon substrate;

[0009] The phenolic resin is spherical;

[0010] The pre-carbonized biomass carbon precursor is a block structure, and the specific surface area of ​​the pre-carbonized biomass carbon precursor is in the range of 200-500 m 2 / g;

[0011] The dopant includes one or more combinations of N, B, P, S, F, and O elements.

[0012] In a third aspect, the present application provides a silicon-carbon material:

[0013] A silicon-carbon material comprising

[0014] a porous carbon substrate comprising a dopant,

[0015] The porous carbon substrate comprises a phenolic resin and a biomass carbon precursor obtained by pre-carbonizing a biomass carbon material.

[0016] The specific surface area of ​​the pre-carbonized biomass carbon precursor is in the range of 200-500 m 2 / g;

[0017] Wherein, the dopant includes one or more combinations of N, B, P, S, F, and O elements;

[0018] Silicon particles deposited in the carbon pores of a porous carbon substrate;

[0019] and a carbon layer deposited on a porous carbon substrate and / or a surface of silicon particles;

[0020] The phenolic resin is spherical; the pre-carbonized biomass carbon precursor is a block structure.

[0021] In a third aspect, the present application provides a method for preparing a silicon-carbon material:

[0022] A method for preparing a silicon-carbon material comprises the following steps:

[0023] 1) Dispersing phenol monomers, aldehyde monomers, and catalysts in water to form solution A; dissolving pre-carbonized biomass carbon precursor, dispersant, and dopant in an organic solvent to form solution B;

[0024] 2) Solution A was slowly poured into solution B to mix, and the mixture was heated to 60 °C, reacted for 3 h, and dried to obtain solid precursor powder C;

[0025] 3) Activating the solid precursor powder C obtained in step 2) to form pores to obtain a porous carbon substrate;

[0026] 4) depositing silicon on the porous carbon substrate obtained in step 3) in an atmosphere of carrier gas and silicon source gas to obtain a composite material;

[0027] 5) The composite material obtained in step 4) is heated, and a carrier gas and a carbon source gas are introduced to perform surface carbon coating to obtain a finished silicon-carbon material;

[0028] The masses of the pre-carbonized porous carbon precursor, the dispersant and the dopant account for 20-50%, 1-10% and 1-5% of the total mass of the phenolic monomer and the aldehyde monomer, respectively.

[0029] The controllable synthesis of the porous carbon substrate in the silicon-carbon material of the present application is to polymerize phenolic monomers and aldehyde monomers in the presence of a catalyst and a dispersant, and at the same time add a dopant and a pre-carbonized biomass carbon precursor to the solution. The phenolic resin formed by the polymerization is a spherical structure, and the homogeneous doping of elements is completed during the synthesis process. The added biomass carbon precursor is a block structure. The combination of carbon-based particles of different structures can better exert their respective beneficial effects, complement each other's strengths and weaknesses, and comprehensively improve battery performance, so that the battery has excellent cycle performance and conductivity; in addition, the biomass carbon precursor can also provide reactive groups to partially replace the amount of phenolic and aldehyde monomers, thereby improving resource utilization and greatly reducing production costs.

[0030] Furthermore, in the step 1), the phenolic monomer includes one or a combination of at least two of phenol, cresol, xylenol, and resorcinol; the aldehyde monomer includes one or a combination of at least two of formaldehyde, acetaldehyde, propionaldehyde, furfural, and acrolein; the catalyst includes one or a combination of at least two of sodium hydroxide, potassium hydroxide, barium hydroxide, ammonia water, and sodium carbonate; the molar ratio of the phenolic monomer to the aldehyde monomer is 1:0.5-3, and the mass of the catalyst accounts for 1-10% of the total mass of the phenolic monomer and the aldehyde monomer.

[0031] Furthermore, in the step 1), the pre-carbonized biomass carbon precursor is obtained by heat treating the biomass carbon material in an inert atmosphere; the biomass carbon material is one or a combination of at least two of coconut shell, fruit shell, straw, bamboo, and lignin; the heat treatment temperature is 200-400°C, and the heat treatment time is 1-4h.

[0032] Further, the dispersant is one or a combination of at least two of Span 80, hexadecyltrimethylammonium bromide, polyvinyl pyrrolidone, and polyvinyl alcohol;

[0033] The dopant is one or a combination of at least two of urea, melamine, boron oxide, boric acid, boron nitride, ammonium dihydrogen phosphate, sodium sulfate, thiourea, polytetrafluoroethylene, silicon tetrafluoride, and hydrogen peroxide;

[0034] The organic solvent is one or a combination of at least two of ethanol, propanol, nitrogen methyl pyrrolidone, acetone and benzene.

[0035] Furthermore, in the step 3), the activation pore-forming is chemical activation or physical activation;

[0036] The chemical activation activator is one or a combination of potassium hydroxide, sodium hydroxide, zinc chloride, potassium carbonate; the mass ratio of the precursor powder to the activator is 1:1-5, the activation treatment temperature is 800-1000°C, and the time is 1-4h;

[0037] The activator of the physical activation is water vapor or carbon dioxide. The specific process is to heat the precursor powder to 800-1000°C and introduce water vapor or carbon dioxide.

[0038] The new silicon-carbon material structure is to first prepare a porous carbon substrate and then deposit carbon particles in the pores. If the pore-forming silicon particles are not activated, they will accumulate on the surface of the material and the electrical performance of the battery will decrease.

[0039] Adding dopants can improve the strength of the carbon skeleton structure, enhance ionic conductivity and reduce impedance.

[0040] Further, the carrier gas is one of nitrogen, argon, and helium, or a combination of at least two of them; the silicon source gas is one of silane, disilane, dichlorosilane, and trichlorosilane, or a combination of at least two of them; the ratio of the carrier gas to the silane gas is 1 to 5:1; the silicon deposition temperature is 400 to 600° C., and the time is 1 to 6 hours;

[0041] The carbon source gas is one or a combination of at least two of acetylene, methane, propylene, acetone, and natural gas;

[0042] The ratio of the carrier gas to the carbon source gas is 1-5:1, the surface carbon coating temperature is 800-1000°C, and the time is 2-6 hours.

[0043] In a fourth aspect, the present application provides a battery negative electrode material:

[0044] A battery negative electrode material comprises the porous carbon substrate of the present application or the silicon-carbon material of the present application or the silicon-carbon material obtained by the preparation method of the present application.

[0045] In a fifth aspect, the present application provides a lithium-ion battery:

[0046] A lithium-ion battery comprises the porous carbon substrate of the present application or the silicon-carbon material of the present application or the silicon-carbon material obtained by the preparation method of the present application.

[0047] Beneficial effects:

[0048] 1) By combining the blocky biomass carbon substrate with the spherical resin-based carbon substrate, a complementary effect is formed. While ensuring the high filling density, good fluidity and uniform force of the spherical carbon substrate during lithium insertion expansion, the bonding strength with the conductive agent and binder is improved, thereby better exerting the long-cycle performance of the material; 2) Element doping is completed while synthesizing the resin carbon, and the structural strength of the carbon skeleton is enhanced by in-situ homogeneous doping, while the lithium ion diffusion coefficient is increased and the impedance is reduced; 3) The biomass carbon precursor can also provide reactive groups to partially replace the amount of phenolic and aldehyde monomers, thereby greatly reducing production costs while improving resource utilization. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 This is a process flow chart of the porous carbon substrate and silicon carbon preparation process of the present invention;

[0050] Figure 2 This is a SEM image of the silicon-carbon material prepared in Example 1 of the present invention;

[0051] Figure 3 This is a SEM image of the silicon-carbon material prepared in Comparative Example 1 of the present invention;

[0052] Figure 4The electrical conductivity performance diagram of the silicon-carbon materials prepared in Examples 1 and 2 of the present invention and Comparative Examples 1 and 2 under different pressures;

[0053] Figure 5 This is a high temperature cycle performance diagram of the silicon-carbon materials prepared in Examples 1 and 2 of the present invention and Comparative Examples 1 and 2. DETAILED DESCRIPTION

[0054] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0055] Example 1, a method for preparing a silicon-carbon material, the specific process flow chart is as follows Figure 1 , including the following steps:

[0056] 1) Phenol, formaldehyde and catalyst ammonia water (mass fraction of ammonia is 25%) are dispersed in deionized water to form solution A; wherein the molar ratio of phenol to formaldehyde is 1:1.2, and the mass of the added ammonia water is 3% of the total mass of phenol and formaldehyde.

[0057] The lignin pre-carbonized in an inert atmosphere (heat treatment temperature of 300-500 °C, heat treatment time of 2 h, specific surface area of ​​200-500 m 2 / g), dispersant Span 80, and dopant melamine are dispersed in ethanol to form solution B, wherein the added amounts of lignin, Span 80, and melamine account for 25%, 2%, and 2% of the total mass of phenol and formaldehyde, respectively.

[0058] 2) Place solution A in a reactor, slowly pour solution B into it while stirring, raise the temperature to 60°C, react for 3 hours, dry the solution, and obtain solid precursor powder C.

[0059] 3) The powder C obtained in step 2) was mixed with the activator KOH in a mass ratio of 1:1.2, heat treated at 950° C. for 3 h, acid washed and dried to obtain a porous carbon substrate.

[0060] 4) The porous carbon substrate obtained in step 3) is placed in a fluidized bed deposition furnace, N2 is introduced, the temperature is raised to 500°C, silane gas is introduced, wherein the flow ratio of silane to N2 is 1:3, and a composite material is obtained after deposition for 6 hours.

[0061] 5) The composite material obtained in step 4) is placed in a rotary kiln, N2 is introduced, the temperature is raised to 500°C, acetylene is introduced, wherein the flow ratio of acetylene to N2 is 1:1, and the finished silicon-carbon material is obtained after deposition for 4 hours. The SEM image of the silicon-carbon material is as follows: Figure 2 .

[0062] Embodiment 2, a method for preparing a silicon-carbon material, comprising the following steps:

[0063] 1) Disperse resorcinol, formaldehyde and catalyst sodium carbonate in deionized water to form solution A, wherein the molar ratio of resorcinol to formaldehyde is 1:1.5, and the mass of added sodium carbonate is 5% of the total mass of resorcinol and formaldehyde.

[0064] The coconut shell charcoal (heat treatment temperature of 300-500 °C, heat treatment time of 2 h, specific surface area of ​​200-500 m2) was pre-carbonized in an inert atmosphere. 2 / g), dispersant hexadecyltrimethylammonium bromide, and dopant boric acid are dispersed in ethanol to form solution B, wherein the added amounts of pre-carbonized coconut shell charcoal, hexadecyltrimethylammonium bromide, and boric acid account for 30%, 3%, and 5% of the total mass of resorcinol and formaldehyde, respectively.

[0065] 2) Place solution A in a reactor, slowly pour solution B into it while stirring, raise the temperature to 60°C, react for 3 hours, dry the solution, and obtain solid precursor powder C.

[0066] 3) Powder C obtained in step 2) is placed in a rotary kiln, nitrogen is introduced, the temperature is raised to 950° C., water vapor is introduced, and the reaction is continued for 4 hours to obtain a porous carbon substrate.

[0067] 4) The porous carbon substrate obtained in step 3) is placed in a fluidized bed deposition furnace, N2 is introduced, the temperature is raised to 550°C, silane gas is introduced, wherein the flow ratio of silane to N2 is 1:2, and a composite material is obtained after deposition for 5 hours.

[0068] 5) The composite material obtained in step 4) is placed in a rotary kiln, N2 is introduced, the temperature is raised to 500°C, acetylene is introduced, wherein the flow ratio of acetylene to N2 is 1:1, and the finished silicon-carbon material is obtained after deposition for 4 hours.

[0069] Comparative Example 1

[0070] The material preparation process is the same as that in Example 1, except that in step 1), no pre-carbonized lignin is added to solution B. The SEM image of the silicon-carbon material is as follows: Figure 3 .

[0071] Comparative Example 2

[0072] The material preparation process is the same as that of Example 1, except that in step 1), no dopant melamine is added to solution B.

[0073] A battery negative electrode material:

[0074] The silicon-based negative electrode materials prepared in Examples 1 and 2 and Comparative Examples 1 and 2 were mixed with commercial artificial graphite with an average particle size of 15 μm in a mass ratio of 7:93 to form a battery negative electrode material with a capacity of 450 mAh / g.

[0075] A battery:

[0076] The active material, adhesive PAA, conductive agent 1 single-arm CNT, and conductive agent 2 carbon black are dispersed and slurried in a ratio of 95.35%: 4.05%: 0.06%: 0.54%, and the aforementioned battery negative electrode material (the silicon-based negative electrode materials prepared in Examples 1, 2 and Comparative Examples 1, 2 are used in turn) is used, and then a small soft-pack battery is made by coating, rolling, slitting and other battery preparation processes in combination with NCM811 positive electrode.

[0077] The conductivity of the finished powder materials prepared in Examples 1 and 2 and Comparative Examples 1 and 2 was tested. The results are as follows: Figure 4 .

[0078] The high temperature cycle performance of the relevant materials on the full battery was tested. The specific test conditions were 1C constant current and constant voltage charging to 4.25V, 1C constant current discharge to 2.8V, and the first cycle capacity was used as the benchmark, and the cycle was terminated when the capacity decayed to 80%. The test results are as follows: Figure 5 .

[0079] From the test results, it can be seen that without adding pre-carbonized lignin (Comparative Example 1), the finished silicon carbon did not mix particles of different structures. Because the perfect spherical particle structure has the problem of loose contact with the conductive agent and adhesive, the cycle decay is fast; without element doping (Comparative Example 2), the impedance of the finished silicon carbon was not effectively reduced, which affected the lithium ion migration efficiency and the cycle life was also reduced.

[0080] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A porous carbon substrate, characterized in that It includes phenolic resin, a biomass carbon precursor obtained by pre-carbonizing a biomass carbon material, and a dopant dispersed in a porous carbon substrate; The phenolic resin is spherical; The pre-carbonized biomass carbon precursor is a block structure, and the specific surface area of ​​the pre-carbonized biomass carbon precursor is in the range of 200-500 m 2 / g; The dopant includes one or more combinations of N, B, P, S, F, and O elements.

2. A silicon-carbon material, characterized in that: include a porous carbon substrate comprising a dopant, The porous carbon substrate comprises a phenolic resin and a biomass carbon precursor obtained by pre-carbonizing a biomass carbon material. The phenolic resin is spherical, the pre-carbonized biomass carbon precursor is a block structure, and the specific surface area of ​​the pre-carbonized biomass carbon precursor is in the range of 200-500 m 2 / g; Wherein, the dopant includes one or more combinations of N, B, P, S, F, and O elements; Silicon particles deposited in the carbon pores of a porous carbon substrate; and a carbon layer deposited on a porous carbon substrate and / or a surface of silicon particles.

3. A method for preparing a silicon-carbon material, characterized in that: The following steps are involved: 1) Dispersing phenol monomer, aldehyde monomer and catalyst in water to form solution A; Dissolving the pre-carbonized biomass carbon precursor, dispersant, and dopant in an organic solvent to form a solution B; 2) Solution A was slowly poured into solution B to mix, and the mixture was heated to 60 °C, reacted for 3 h, and dried to obtain solid precursor powder C; 3) Activating the solid precursor powder C obtained in step 2) to form pores to obtain a porous carbon substrate; 4) depositing silicon on the porous carbon substrate obtained in step 3) in an atmosphere of carrier gas and silicon source gas to obtain a composite material; 5) The composite material obtained in step 4) is heated, and a carrier gas and a carbon source gas are introduced to perform surface carbon coating to obtain a finished silicon-carbon material; The masses of the pre-carbonized porous carbon precursor, the dispersant and the dopant account for 20-50%, 1-10% and 1-5% of the total mass of the phenolic monomer and the aldehyde monomer, respectively.

4. The method for preparing a silicon-carbon material according to claim 3, characterized in that: In the step 1), the phenolic monomer comprises one or a combination of at least two of phenol, cresol, xylenol, and resorcinol; the aldehyde monomer comprises one or a combination of at least two of formaldehyde, acetaldehyde, propionaldehyde, furfural, and acrolein; the catalyst comprises one or a combination of at least two of sodium hydroxide, potassium hydroxide, barium hydroxide, ammonia water, and sodium carbonate; the molar ratio of the phenolic monomer to the aldehyde monomer is 1:0.5-3, and the mass of the catalyst accounts for 1-10% of the total mass of the phenolic monomer and the aldehyde monomer.

5. The method for preparing a silicon-carbon material according to claim 3, characterized in that: In the step 1), the pre-carbonized biomass carbon precursor is obtained by heat treating the biomass carbon material in an inert atmosphere; the biomass carbon material is one or a combination of at least two of coconut shell, fruit shell, straw, bamboo, and lignin; the heat treatment temperature is 200-400°C, and the heat treatment time is 1-4h.

6. The method for preparing a silicon-carbon material according to claim 3, characterized in that: The dispersant is one or a combination of at least two of Span 80, hexadecyltrimethylammonium bromide, polyvinyl pyrrolidone and polyvinyl alcohol; The dopant is one or a combination of at least two of urea, melamine, boron oxide, boric acid, boron nitride, ammonium dihydrogen phosphate, sodium sulfate, thiourea, polytetrafluoroethylene, silicon tetrafluoride, and hydrogen peroxide; The organic solvent is one or a combination of at least two of ethanol, propanol, nitrogen methyl pyrrolidone, acetone and benzene.

7. The method for preparing a silicon-carbon material according to claim 3, characterized in that: In the step 3), the activation pore-forming is chemical activation or physical activation; The chemical activation activator is one or a combination of potassium hydroxide, sodium hydroxide, zinc chloride, and potassium carbonate; the mass ratio of the precursor powder to the activator is 1:1-5, the activation treatment temperature is 800-1000°C, and the time is 1-4 h; The activator of the physical activation is water vapor or carbon dioxide. The specific process is to heat the precursor powder to 800-1000°C and introduce water vapor or carbon dioxide.

8. The method for preparing the porous carbon substrate and the silicon-carbon material according to claim 3, characterized in that: The carrier gas is one of nitrogen, argon, and helium, or a combination of at least two of them; the silicon source gas is one of silane, disilane, dichlorosilane, and trichlorosilane, or a combination of at least two of them; the ratio of the carrier gas to the silicon source gas is 1-5:1; the silicon deposition temperature is 400-600° C., and the time is 1-6 hours; The carbon source gas is one or a combination of at least two of acetylene, methane, propylene, acetone, and natural gas; The ratio of the carrier gas to the carbon source gas is 1-5:1, the surface carbon coating temperature is 800-1000°C, and the time is 2-6 hours.

9. A battery negative electrode material, characterized in that: It comprises the porous carbon substrate as claimed in claim 1 or the silicon-carbon material as claimed in claim 2 or the silicon-carbon material obtained by the preparation method as claimed in any one of claims 3 to 8.

10. A lithium ion battery, characterized in that: It comprises the porous carbon substrate as claimed in claim 1 or the silicon-carbon material as claimed in claim 2 or the silicon-carbon material obtained by the preparation method as claimed in any one of claims 3 to 8.

Citation Information

Patent Citations

  • Silicon-carbon composite material and preparation method thereof, secondary battery and electric device

    CN117096330A

  • Coconut shell-phenolic resin-based silicon-carbon composite material and preparation and application thereof

    CN117727918A

  • Multi-element doped porous carbon and preparation method thereof, silicon-carbon negative electrode material and preparation method and application of silicon-carbon negative electrode material

    CN118851172A

  • Rate type silicon-carbon material as well as preparation method and application thereof

    CN119340371A

  • Porous Composite Material Capable of Generating Electric Arc in Microwave Field, Preparation Method therefor, and Use thereof

    US20220008882A1

Cited By

  • Resin-based self-activated porous carbon material as well as preparation method and application thereof

    CN120081369A

  • Preparation method of carbon-based graded porous biological electrode material of biomass-resin composite material

    CN120664684A

  • Solid electrolyte doped silicon-carbon composite material, preparation method and application thereof

    CN121076100A

  • Solid-state electrolyte doped silicon-carbon composite material, preparation method and application thereof

    CN121076100B

  • Spherical resin sphere and spherical porous carbon suitable for silicon-carbon negative electrode and preparation method of spherical resin sphere and spherical porous carbon

    CN121076115A